Peak fat oxidation, peak oxygen uptake, and running performance increase during pre-season in sub-elite male football players - Rømer, T.; Hansen, M. T.; Lange, K. K.; Petersen, M. L.; Petersen, A.; Panduro, J.; Krustrup, P.; Dela, F.; Helge, J. W. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Purpose In Football, the high-intensity running bouts during matches are considered decisive. Interestingly, recent studies showed that peak fat oxidation rates (PFO) are higher in football players than other athletes. This study aimed to investigate whether PFO increases following a pre-season. Secondarily, and due to COVID-19, we investigated whether PFO is related to the physical performance in a subgroup of semi-professional male football players.